FAKTOR SOSIAL YANG MEMPENGARUHI PERUBAHAN BAHASA DALAM MASYARAKAT - Ja'a Nazielatu Rois Nabilla; Wiwik Yulianti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
This study discusses about language changes that exist in people's daily conversations. The language change that occurs is based on social factors, especially the social class of the society. This study describes about the language changes that exist in the surrounding community by looking at the factors and social class of the community and to describe the language chosen by the society based on the social class of the society. This research is qualitative research that has data in the form of society utterances that have changed according to the social class of the society. Data sources in this study are people who live in the environment around the writer. This research method uses the listen and note method. Researchers will identify speech that undergoes language changes based on three social classes of society, such as: upper social class, middle and lower. This study found differences in some language change use in daily conversation of the three social classes of society. The result of the study, the writer found 51 utterances that experienced about language changes based on the social class of the society, including (1) 21 utterances from the upper social class, (2) 19 utterances from the middle social class, and (3) 11 utterances from the lower social class. Keywords: language change, social factor, society